The Slovenian Philharmonic after the Second World War - from ideology and professional disputes to art - Bogunović Hočevar, Katarina (Muzikološki zbornik, 2014)
Alongside the previously formed aspirations of the Slovenian music scene, the post-war period brought new opportunities and challenges. Immediately after its founding, the newly established Slovenian Philharmonic began to realise the idea of collectivism. Soon after its affirmation, however, it started to shift away from this ideal and seek a path towards a firmer programme policy. On this path, it also had to overcome certain (sometimes well-intentioned) obstacles arising from various professional societies.
Keywords: Društvo slovenskih skladateljev; koncertne poslovalnice; Slovenian Philharmonic Orchestra; Slovenska filharmonija; slovenski glasbeni prostor; Škerjanc, Lucijan Marija, 1900-1973